Correction: Observation of crystalline changes of titanium dioxide during lithium insertion by visible spectrum analysis. Issue 37 (15th September 2017) - Nam, Inho; Park, Jongseok; Park, Soomin; Bae, Seongjun; Yoo, Young Geun; Han, Jeong Woo; Yi, Jongheop
Abstract : Correction for 'Observation of crystalline changes of titanium dioxide during lithium insertion by visible spectrum analysis' by Inho Nam et al., Phys. Chem. Chem. Phys., 2017, 19, 13140–13146.